2002
DOI: 10.1046/j.1525-1438.2002.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of the peritoneal cavity: Relevance for host-tumor relation

Abstract: The peritoneal membrane, formed by a single layer of mesothelial cells, lines the largest cavity of the human body. Anatomic structures of the peritoneal cavity, along with resident leukocyte populations, play an important role in the defense against microorganisms invading by breaching the gut integrity or ascending through the female genital tract. Local immune mechanisms in the peritoneal cavity are also important in patients undergoing peritoneal dialysis and in women with endometriosis. There is now exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 109 publications
1
29
0
Order By: Relevance
“…39,40 This macrophage population represents the first line of defense against microbes breaching the intestine and ascendant gynecological infections. 22 As has been reported for other sites, 41-43 we observed that the peritoneal administration of IL-33 was able to promote an allergic like macrophage activation in the peritoneal tumor-associated macrophages. As reported previously for CD40 activated CD86 + activated macrophages in the microenvironment of pancreatic cancer, 44 or activated peritoneal macrophages were able to promote tumor cytotoxicity in vitro and delay tumor progression in vivo.…”
Section: Discusionsupporting
confidence: 76%
See 1 more Smart Citation
“…39,40 This macrophage population represents the first line of defense against microbes breaching the intestine and ascendant gynecological infections. 22 As has been reported for other sites, 41-43 we observed that the peritoneal administration of IL-33 was able to promote an allergic like macrophage activation in the peritoneal tumor-associated macrophages. As reported previously for CD40 activated CD86 + activated macrophages in the microenvironment of pancreatic cancer, 44 or activated peritoneal macrophages were able to promote tumor cytotoxicity in vitro and delay tumor progression in vivo.…”
Section: Discusionsupporting
confidence: 76%
“…Therefore, the peritoneal cavity has a resident population of ontogenically differentiated resident macrophages that serve as first line of defense. 22 Allergic reactions are characterized by the presence of an activated macrophages, also described as wound-healing or M2a macrophages. 23-25 Accordingly, we found that peritoneal macrophages presented this allergic like activated phenotype shown by an increased production of Ym-1 and IL-13 (Figure 5a &b ).…”
Section: Resultsmentioning
confidence: 99%
“…There is now emerging evidence that a significant innate and adaptive immunity exists in the peritoneum that prevents the successful growth and propagation of tumor cells. 64 This immunity may be subverted by some tumors, allowing them to grow. The malignant potential of tumor cells within the peritoneal cavity may also be related to the number of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, malignant effusions as a sample matrix are often overlooked. In addition to the identification of biomarkers that characterize the tumor cell, the analysis of malignant effusions could be useful specifically in the monitoring of the host antitumor response [22]. For example, in malignant ascites of patients with advanced malignancies the phenotype of leukocytes consistent with defective antigen presentation and costimulatory pathway have been observed [12,14].…”
mentioning
confidence: 99%